Reshaping Croatian National Identity - The story about National Museum - Vujić, Žarka; Babić, Darko (2006)
The history of the museums and the relationship between museums and national identity in Croatia to date could be succinctly described as a long journey, full of difficulties and delays in the outset.
Projekt MZOS
ENG